The surface coating of iron oxide nanoparticles drives their intracellular trafficking and degradation in endolysosomes differently depending on the cell type. (February 2022) - Portilla, Yadileiny; Mulens-Arias, Vladimir; Paradela, Alberto; Ramos-Fernández, Antonio; Pérez-Yagüe, Sonia; Morales, M. Puerto; Barber, Domingo F.
Abstract: Magnetic nanoparticles (MNPs) are potential theranostic tools that are biodegraded through different endocytic pathways. However, little is known about the endolysosomal network through which MNPs transit and the influence of the surface coating in this process. Here, we studied the intracellular transit of two MNPs with identical iron oxide core size but with two distinct coatings: 3-aminopropyl-trietoxysilane (APS) and dimercaptosuccinic acid (DMSA). Using endolysosomal markers and a high throughput analysis of the associated proteome, we tracked the MNPs intracellularly in two different mouse cell lines, RAW264.7 (macrophages) and Pan02 (tumor cells). We did not detect differences in the MNP trafficking kinetics nor in the MNP-containing endolysosome phenotype in Pan02 cells. Nonetheless, DMSA-MNPs transited at slower rate than APS-MNPs in macrophages as measured by MNP accumulation in Rab7 + endolysosomes. Macrophage DMSA-MNP-containing endolysosomes had a higher percentage of lytic enzymes and catalytic proteins than their APS-MNP counterparts, concomitantly with a V-type ATPase enrichment, suggesting an acidic nature. Consequently, more autophagic vesicles are induced by DMSA-MNPs in macrophages, enhancing the expression of iron metabolism-related genes and proteins. Therefore, unlike Pan02 cells, the MNP coating appears to influence the intracellular trafficking rate and the endolysosome nature in macrophages. These results highlight how the MNP coating can determine the nanoparticle intracellular fate and biodegradation in a cell-type bias.